Metabolite profiling, in vitro antioxidant and a-glucosidase inhibitory properties of Timonius ternifolius leaves (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Vivit MB, Batuyong RG, Damian AFT, Gaoat CA, Beltran KGD, Alejo AB, Calaramo MA, Ibana FV, Batuyong MAR. 2024. Metabolite profiling, in vitro antioxidant and a-glucosidase inhibitory properties of Timonius ternifolius leaves. Biodiversitas 25: 3027-3034. The genus Timonius (Rubiaceae) possesses different pharmacological properties. One understudied endemic species under this genus from the Philippines is the Timonius ternifolius (Bartl. ex DC.) Fern.-Vill. Hence, this study investigates the physicochemical properties and phytochemical constituents of the leaf ethanolic extract (EE) and subjected to solvent partitioning to yield the following subfractions: hexane (HE), ethyl acetate (EA), and methanol (ME) extracts, which were utilized for the in vitro antioxidant, a-glucosidase and a-amylase assays. Quantitative tests of T. ternifolius leaves revealed the following physicochemical properties: herbal tea-like odor, fibrous and fluffy appearance, 50.07% moisture content, 3.10% total ash content, and a slightly acidic pH value of 5.13. The liquid chromatography-mass spectrometry (LC-MS) analysis has identified eight putative compounds namely glabrolide, aloinoside B, 2-benzyl octanal, geumonoid, (±) gomisin M1, 25-O-Acetyl-7,8-didehydrocimigenol-3-O-a-D-xylopyranoside, lucialdehyde B, and kadsuric acid. The extracts' concentrations of flavonoids, phenols, and terpenoids were 1.23±0.19 mg QE/g, 20.77±0.77 mg GAE/g, and 6.07±0.53 mg/g, respectively. Antioxidant profiling among the subfractions showed EE exhibiting the highest at 59.15±2.08 µg/mL (IC50 value). Moreover, significant a-glucosidase inhibition was noted in the EE extract at 99.74%, EA at 99.71%, and ME at 99.45%. The results showed that T. ternifolius leaves are a promising lead source of pharmacologically active compounds with antioxidant and antidiabetic activities, expanding information on plant-derived alternative treatments and developing medicinal products.